Police Officer performance and perception using light, medium and heavy weight tactical batons. (February 2019) - MacIntosh, Alexander R.; Desmoulin, Geoffrey T.
Abstract: Objective: Compare the effectiveness of light, medium and heavy weight Police expandable batons from a performance and a user perception perspective. Rationale: Police Officers are required to control combative individuals using less lethal tactics in proportion to the threat they face. Officers need to deliver sufficient force quickly and accurately. As such, it is important to select batons that are optimal for both performance and user experience. Methods: Eleven active-duty New York Police Department Officers completed static and dynamic strike testing followed by a questionnaire. Six baton types were tested using different weights and lengths. Results: Peak force, dynamic task speed and accuracy were similar between baton types. Peak impulse, forearm muscle activity, and discomfort were higher with the heaviest baton. Conclusions: Lighter batons can deliver sufficient force to control assailants while imposing lower ergonomic costs and being preferable to the user with no impact on speed or accuracy. Highlights: Use of all batons tested generated forces sufficient to cause fractures. Light batons can deliver sufficient force while imposing lower ergonomic cost than heavier batons. Similarity in performance across baton weight classes highlights the importance of considering the user in assigning batons.